Description of a new Geodipsas snake from northern Madagascar (Squamata: Colubridae) - Mercurio, Vincenzo; Andreone, Franco (Zootaxa, 2005)
We describe a new species of the colubrid snake genus Geodipsas from the rainforests of the Anjanaharibe-Sud and Tsaratanana massifs, northern Madagascar. Geodipsas fatsibe n. sp. differs from the other described species of the genus in the following characteristics: 21 rows of dorsal scales at midbody, high number of ventral (198) scales and by the presence of very large hooked spines on the hemipenis. Geodipsas fatsibe is most similar to Geodipsas infralineata. Most likely they are sister species, with a vicariant northern vs. central southern distribution.